PENGARUH PENGIKATAN ALAT KONTRASEPSI DALAM RAHIM TERHADAP KONTINUITAS PADA PEMASANGAN KELUARGA BERENCANA PASCA SALIN METODE TRANSESAREA - Ariadi, Ariadi; Bachtiar, Hafni (Andalas Obstetrics And Gynecology Journal, 2018)
The insertion of an intrauterine device (IUD) is installed immediately after delivery has been recommended by the WHO, as one method of contraception is safe and effective for interim and prevent missed opportunity (unmet need). IUD insertion after childbirth can avoid the discomfort that usually occurs during the interval insertion, and lochia can obscure any bleeding from the insertion. However, post-partum IUD insertion has disadvantages as well. The risk of the possibility of spontaneous expulsion is very high. This study is an experimental study with the method of post-test control group design to determine differences in IUD expulsion rate tied and not tied when installed during caesarean section at RSUP. Dr.M.Djamil in Padang, and Military Hospital Reksodiwiryo Padang and Painan District Hospital. There were no significant differences between trancaesarean IUD insertion methods that are not tied or tied (P> 0.05). The percentage of expulsion is not tied 11.4% higher compared to 0% tied expulsion. Statistically, were not significant differences as obtained P value> 0.05.Keywords: IUD, tied, trancaesarean